Solution state characterization of polyvinyl pyrrolidone (PVP) wrapped indomethacin / Norhafiza Ismail @ Abdul Rashid - Ismail @ Abdul Rashid, Norhafiza (2013)
Indomethacin is an acidic non-steroidal anti-inflammatory agent that used mainly for the relief of pain and severe inflammation in the treatment of rheumatic disease and similar disorders. Indomethacin is a poorly water-insoluble drug that leads to low absorption and bioavailability. The solution state characterization of polyvinyl pyrrolidone (PVP) wrapped was studied by using saturation solubility, drug content assay and dissolution efficiency. The standard plot was calibrated after obtained R2 = 0.9992. From the experiment, polyvinyl pyrrolidone wrapped indomethacin samples D (PVP-IDM-D) was showed maximum saturation solubility, 21.5 fold while the minimum saturation solubility is polyvinyl pyrrolidone wrapped indomethacin samples A (PVP-IDM-A), 8.63 fold. From the drug content assay, PVP-IDM-D showed 13.64% drug presence as compared to pure IDM with 96.94%. The dissolution study revealed a good result with 97.38% drug dissolved for PVP-IDM-D compared to 5.19% for pure IDM. In this study the results of the saturation solubility study and the dissolution study are complimenting each other.